2021
DOI: 10.3390/ijerph18126656
|View full text |Cite
|
Sign up to set email alerts
|

An Early Collaborative Intervention Focusing on Parent-Infant Interaction in the Neonatal Period. A Descriptive Study of the Developmental Framework

Abstract: Moderate to late preterm infants are at risk of developing problems later in life. To support attachment and infants’ development, high quality parent-infant interaction is important. Parent-infant interaction is known to improve through intervention programs but since no such intervention program is addressed directly to moderate to late preterm infants, a tailor-made intervention was developed. The aim was to describe the rationale, development, framework and practical provision of a new early collaborative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The Family Nurture Intervention and Family Integrated Care focus on integrating parents and family members as partners in the infant’s care, including daily calming, nurturing, and interaction activities in NICUs [ 43 , 44 ]. Most recently, a Swedish group developed the Early Collaborative Intervention program to facilitate early parent-infant interactions that start within the first days of the infant’s life [ 45 ].…”
Section: Parent Participation In Infant Carementioning
confidence: 99%
See 1 more Smart Citation
“…The Family Nurture Intervention and Family Integrated Care focus on integrating parents and family members as partners in the infant’s care, including daily calming, nurturing, and interaction activities in NICUs [ 43 , 44 ]. Most recently, a Swedish group developed the Early Collaborative Intervention program to facilitate early parent-infant interactions that start within the first days of the infant’s life [ 45 ].…”
Section: Parent Participation In Infant Carementioning
confidence: 99%
“…43,44) Most recently, a Swedish group developed the Early Collaborative Intervention program to facilitate early parent-infant interactions that start within the first days of the infant's life. 45) While most of these FCC models have focused on edu-cating or supporting parents to enhance their coping skills and parenting capacity, the Close Collaboration with Parents (CCP) program developed in Finland aims to train NICU staff to improve their skills in collaboration with parents and promote FCC. 46) Historically, many NICUs have failed to recognize parents as partners, and parents have reported that they are insufficiently included in their infants' care.…”
Section: Parent Participation In Infant Care 1 Parental Role In Fccmentioning
confidence: 99%
“…These are added to the written summary, for the parents to easier recall details from the session. An example of a written summary is supplemented with the published detailed description of the EACI (Helmer et al, 2021). As the EACI is a new intervention, a randomised controlled study is currently in progress to evaluate the quantitative effects of the program.…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%
“…The EArly Collaborative Intervention (EACI) program is a new early intervention, developed to support interaction between parents and their preterm infants (Helmer et al, 2021). The intervention along with the theoretical framework is described previously (Helmer et al, 2021), and a summary is outlined below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation